2013
DOI: 10.12659/msm.883807
|View full text |Cite
|
Sign up to set email alerts
|

Recreational music-making alters gene expression pathways in patients with coronary heart disease

Abstract: BackgroundPsychosocial stress profoundly impacts long-term cardiovascular health through adverse effects on sympathetic nervous system activity, endothelial dysfunction, and atherosclerotic development. Recreational Music Making (RMM) is a unique stress amelioration strategy encompassing group music-based activities that has great therapeutic potential for treating patients with stress-related cardiovascular disease.Material/MethodsParticipants (n=34) with a history of ischemic heart disease were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…These investigators documented significant changes in NK cell activity and in the level of gene expression for IFN-γ and IL-10. A recent study by Bittman et al [ 57 ] has confirmed the above-mentioned findings on a genetic level: their results support the hypothesis that different sets of genes play important roles in both stress and the relaxation response in humans. If these findings can be confirmed by other research groups, the implications may be of particular importance: they could provide a means for tailored music therapy by identifying the patients who would benefit the most from the clinical effect of music.…”
Section: Music and Medicinesupporting
confidence: 54%
“…These investigators documented significant changes in NK cell activity and in the level of gene expression for IFN-γ and IL-10. A recent study by Bittman et al [ 57 ] has confirmed the above-mentioned findings on a genetic level: their results support the hypothesis that different sets of genes play important roles in both stress and the relaxation response in humans. If these findings can be confirmed by other research groups, the implications may be of particular importance: they could provide a means for tailored music therapy by identifying the patients who would benefit the most from the clinical effect of music.…”
Section: Music and Medicinesupporting
confidence: 54%
“…In addition, Koyama et al (73) noted that recreational music modulates immunological responses with significant increases of lymphocytes, T cells, CD4 + T cells and memory T cells and higher levels of IFN-γ and IL-6. A more recent study by Bittman et al (74) confirmed the above-mentioned findings on a genetic level: their results support the hypothesis that different sets of genes play important roles in both stress and the relaxation response in humans. All these changes may have a huge impact on skin barrier function and the symptomatology of AD patients.…”
Section: Lifestyle Factors and Leisure Activities In Atopic Dermatitismentioning
confidence: 52%
“…Music is capable of inducing powerful physiological and psychological emotional states (Bittman et al, 2013;Castillo-Pérez, Gómez-Pérez, Velasco, Pérez-Campos, & Mayoral, 2010).…”
Section: Effects Of Pitch and Timing Expectancy On Musical Emotionmentioning
confidence: 99%